Progress in Cryptology - AFRICACRYPT 2012 5th International Conference on Cryptology in Africa, Ifrance, Morocco, July 10-12, 2012. Proceedings - Mitrokotsa, Aikaterini; Vaudenay, Serge; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 5th International Conference on the Theory and Application of Cryptographic Techniques in Africa, AFRICACRYPT 2011, held in Ifrane, Morocco, in July 2012. The 24 papers presented together with abstracts of 2 invited talks were carefully reviewed and selected from 56 submissions. They are organized in topical sections on signature schemes, stream ciphers, applications of information theory, block ciphers, network security protocols, public-key cryptography, cryptanalysis of hash functions, hash functions: design and implementation, algorithms for public-key cryptography, and cryptographic protocols.
Keywords: Computer science; Computer Communication Networks; Data protection; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Information Systems; Computer Science; Data Structures, Cryptology and Information Theory; Data Encryption; Systems and Data Security; Computer Communication Networks; Coding and Information Theory; Management of Computing and Information Systems